PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) SEMBADA MERAH DENGAN PEMBERIAN MACAM PUPUK KANDANG DAN DOSIS PUPUK NPK - Rijal, Rijaidinsyah; Zamroni; Pamungkas, Djoko Heru; Widata, Sri; Sumarwoto (JURNAL ILMIAH AGROUST, 2024)
This study aims to determine the effect of the type of manure and the dosage of Phonska NPK fertilizer which was tested on red sage plants. This research was conducted at "Lestari Makmur" which is located in the Sedayu sub-district, Bantul Yogyakarta which is the location of the Independent Rural Agricultural Research Center. This study used a Completely Randomized Block Design (RAKL), divided into two treatment factors. The first factor is the type of manure including chicken manure (K1), goat manure (K2), cow manure (K3). The second factor concerns Phonska NPK fertilizer which has a dose of 200 kg/ha (D1), 300 kg/ha (D2), and 400 kg/ha (D3). The treatment is divided into three blocks, each block has a different treatment; in the first block, chicken manure mixed with NPK doses of 200, 300, 400 kg/ha, in the second block, goat manure mixed with NPK doses of 200, 300, 400 kg/ha, in the third block, chicken manure mixed with doses NPK 200, 300, 400 kg/ha. The results of this study showed that the various types of manure with NPK doses showed different results. At Phonska NPK fertilizer with a dose of 200 showed higher cow manure than goat manure and chicken manure. Meanwhile, at a dose of 300 kg/ha, chicken manure gave higher yields than cow manure and goat manure. Meanwhile, at a dose of 400 kg/ha, chicken manure and cow manure gave a higher value than goat manure. The conclusion shows that cow manure, goat manure and chicken manure with different Phonska NPK fertilizer doses can provide good growth for the development of red sesame plants .Keywords: manure, NPK fertilizer, red sembada.